Early postoperative recovery after intracranial surgical procedures. Comparison of the effects of sevoflurane and desflurane - Gökçek,Erhan (2016)
ABSTRACT PURPOSE: To compared the effects of sevoflurane and desflurane on early anesthesia recovery in patients undergoing to craniotomy for intracranial lesions. METHODS: After IRB approval, the study included 50 patients aged 18-70 years who had ASA physical statuses of I-II and were scheduled for intracranial surgery. Patients were randomly divided into two groups: sevoflurane and desflurane. Anaesthesia was routinely induced in all patients followed by desflurane 5%-6% or sevoflurane 1%-2%. Moreover remifentanil infusion (0.05-0.2 mcg/kg/min) was adjusted to maintain mean arterial pressure (MAP) within 20% baseline and heart rate <90 bpm. Postoperatively, patients were evaluated over time for responses to painful stimulus, eye opening, hand squeezing, extubation, orientation and time required to achieve a Modified Aldrete Score of 9-10. Parametric and non-parametric data were assessed using Student's t- and Mann-Whitney U tests, respectively. A p<0.05 was taken as statistically significant. RESULTS: The times to responses to painful stimuli (7.7±2.7 vs. 4.8±1.7 min.; p<0.001), emergence (9.5±2.81 vs. 6.3±2.2 min.; p<0.001), hand-squeezing (12.1±2.9 vs. 8.2±2.3 min.; p<0.001), extubation (10.1±2.87 vs. 7.1±1.6 min.; p<0.001), orientation (15.3±3.2 vs. 10.3±2.7 min.; p<0.001) and Aldrete score of 9-10 (23.3±6.1 vs. 15.8±3.8 min.; p<0.001) were significantly lower with desflurane-based anaesthesia vs. sevoflurane-based anaesthesia. CONCLUSION: Desflurane yields early recovery functions and facilitates early postoperative neurologic examinations of intracranial surgery patients.